Cover Crop Mixture Effects on Maize, Soybean, and Wheat Yield in Rotation. Issue 1 (1st March 2019) - Hunter, Mitchell C.; Schipanski, Meagan E.; Burgess, Macdonald H.; LaChance, James C.; Bradley, Brosi A.; Barbercheck, Mary E.; Kaye, Jason P.; Mortensen, David A.
Abstract : Core Ideas: Few studies report the effects of cover crop mixtures on crop yields in rotation. Cover crop C/N ratio was negatively correlated with maize yield. Multispecies mixtures did not affect maize, soybean, or wheat yields. Cover crops with high biomass and C/N ratios provide unique ecosystem services. Both mixtures and diverse rotations may enhance cover crop ecosystem services. Despite the popularity of multispecies cover crop mixtures, there is little published evidence of their effects on subsequent crop yields, especially for multiple crops grown in rotation. We examined the effects of fall‐planted cover crops—both mixtures and their component monocultures—on subsequent crop yields in an organically managed maize ( Zea mays L.)–soybean [ Glycine max (L.) Merr.]–winter wheat ( Triticum aestivum L.) rotation in central Pennsylvania. We hypothesized that cover crop biomass C/N ratio would be negatively correlated with crop yields. This held true for maize ( R 2 = 0.134, p < 0.0001), but there was no cover crop effect on soybean or wheat yields. All multispecies mixtures produced high biomass, and none affected maize yield relative to fallow. Our findings suggest that both multispecies cover crops and diverse crop rotations may increase opportunities to gain the benefits of cover crops with high biomass and C/N ratio—such as erosion control, weed suppression, N retention, and soil C accumulation—without compromising yield.